Refractory case of myelin oligodendrocyte glycoprotein antibody‐associated encephalomyelitis with lumbosacral radiculitis. Issue 2 (13th February 2020) - Nakamura, Masashi; Fujimori, Juichi; Kobayashi, Michiko; Ishigaki, Aya; Kikuchi, Hirokazu; Miyazawa, Koichi; Sato, Kazuhiko; Kawasaski, Emiko; Suzuki, Yasushi; Nakashima, Ichiro
Abstract: Background: Myelin oligodendrocyte glycoprotein antibody (MOG‐IgG) has been identified in demyelinating diseases of the central nervous system, including neuromyelitis optica spectrum disorders (NMOSD) without the presence of anti‐aquaporin‐4 antibody. Patients with MOG‐IgG present with clinical symptoms distinct from those of multiple sclerosis or NMOSD, so MOG‐IgG‐associated encephalomyelitis (MOG‐EM) is regarded as an entity distinct from multiple sclerosis and NMOSD. In contrast to NMOSD with anti‐aquaporin‐4 antibody, MOG‐EM has been reported to respond well to steroid therapy, and the functional prognosis of this disease is good. However, here we report a patient with MOG‐EM and lumbosacral radiculitis who showed little response to various immune therapies. Case presentation: A 40‐year‐old man presented with acute paraplegia and sensory disturbance in the lower body. MOG‐IgG was positive both in serum and cerebrospinal fluid. Steroid pulse therapy, plasma exchange, intravenous immunoglobulin and cyclophosphamide pulse therapy were ineffective. In nerve conduction studies, compound muscle action potentials and F‐waves were not evoked in bilateral lower limb nerves, suggesting severe damage of peripheral nerves and lower motor neurons. Gadolinium enhancement was observed in the cauda equina. Conclusions: The mechanisms of peripheral nerve system involvement in MOG‐EM are unknown, but the present case suggests that MOG‐EM might occasionally combine with peripheral nerve system disturbance. Lumbosacral radiculitis combined with MOG‐IgG can be refractory, and serious sequela might be observed. Abstract : The cauda equina showed gadolinium enhancement in a myelin oligodendrocyte glycoprotein antibody‐associated encephalomyelitis patient.